Real Effects of a Widespread CSR Reporting Mandate: Evidence from the European Union's CSR Directive - FIECHTER, PETER; HITZ, JÖRG‐MARKUS; LEHMANN, NICO (Journal of Accounting Research, 2022)
ABSTRACT We investigate real effects of a widespread corporate social responsibility (CSR) reporting mandate. In 2014, the European Union (EU) passed Directive 2014/95 (hereafter, “CSR Directive”), mandating large listed EU firms to prepare annual nonfinancial reports beginning from fiscal year 2017 onward. We document that firms within the scope of the directive respond by increasing their CSR activities and that they start doing so before the entry‐into‐force of the directive. These real effects are concentrated in firms that are plausibly more strongly affected by the directive, that is, those with previously low levels of both CSR reporting and CSR activities. Using various alternative outcome variables (e.g., new CSR initiatives, improvements in CSR infrastructure, or firm performance), we show that these real effects reflect meaningful increases in CSR beyond firms’ potential attempts to “greenwash” CSR performance. Finally, we conduct tests that increase our confidence that the documented real effects are attributable to the CSR Directive and not general EU trends in CSR.